1+2+...+n+(n-1)+...+1 = n^2/Proof 4

From ProofWiki
Jump to navigation Jump to search

Theorem

$\forall n \in \N: 1 + 2 + \cdots + n + \left({n-1}\right) + \cdots + 1 = n^2$


Proof

Let $T_n = 1 + 2 + \cdots + n + \left({n - 1}\right) + \cdots + 1$.

We have $T_1 = 1$

and

\(\displaystyle T_n - T_{n-1}\) \(=\) \(\displaystyle \left({1 + 2 + \cdots + n + \left({n - 1}\right) + \cdots + 1 }\right)\) Definition of $T_n$
\(\displaystyle \) \(\) \(\, \displaystyle - \, \) \(\displaystyle \left({1 + 2 + \cdots + \left({n - 1}\right) + \left({n - 2}\right) + \cdots + 1}\right)\)
\(\displaystyle \) \(=\) \(\displaystyle \left({\left({1 + 2 + \cdots + n}\right) - \left({1 + 2 + \cdots + \left({n - 1}\right)}\right)}\right)\) Integer Addition is Associative
\(\displaystyle \) \(\) \(\, \displaystyle + \, \) \(\displaystyle \left({\left({\left({n - 1}\right) + \left({n - 2}\right) + \cdots + 1}\right) - \left({\left({n - 2}\right) + \left({n - 3}\right) + \cdots + 1}\right)}\right)\) Integer Addition is Commutative
\(\displaystyle \) \(=\) \(\displaystyle n + \left({n - 1}\right)\) simplifying
\(\displaystyle \) \(=\) \(\displaystyle 2 n - 1\)

Thus we have:

\(\displaystyle T_n\) \(=\) \(\displaystyle \left({T_n - T_{n-1} }\right) + \left({T_{n-1} - T_{n-2} }\right) + \cdots + \left({T_2 - T_1}\right) + T_1\)
\(\displaystyle \) \(=\) \(\displaystyle \left({2 n - 1}\right) + \left({2 \left({n - 1}\right) - 1}\right) + \cdots + \left({2 \times 2 - 1}\right) + 1\)
\(\displaystyle \) \(=\) \(\displaystyle \sum_{k \mathop = 1}^n 2 k - 1\)
\(\displaystyle \) \(=\) \(\displaystyle n^2\) Odd Number Theorem


$\blacksquare$